The Survey on vaccination and infection of middle school students after the full liberalization of COVID-19 - Liu, Yanping (Pacific International Journal, 2023)
Objective To explore the situation of COVID-19 vaccination and infection among middle school students after the full liberalization of [the]COVID-19 restraciation, and to provide theoretical basis and support for health reflection after the epidemic. Methods On the basis of convenient sampling, A cluster sampling method was adopted. In February 2023, a survey was carried out among all the students in a town[A] level middle school in the southeast of Henan Province in China. Their general information, COVID-19 vaccination and infection data were obtained in the form of questionnaire stars. To explore the vaccination and infection of COVID-19 among middle scho[]ol students with different characteristics, and to conduct multifactor logistic regression analysis on the independent variables of different grades of middle school students, the length of sleep every day, daily exercise duration, whether they have underlying diseases, monthly families income , and the vaccination status as independen[independent ]t variables. and the dependent variables of infection such as those who have not been infected with COVID-19, who have been infected with COVID-19 once, who have been infected with COVID-19 twice, and who have symptoms but have not undergone nucleic acid testing. Results After the COVID-19 pandemic, there were 57 middle school students receiving the COVID-19 vaccine ≤1 dose, accounting for 4.54%. 794 people (63.32%) were inoculated with 2 doses; 403 patients received 3 doses, accounting for 32.14%. The number of people who were not infected was 413, accounting for 32.93%; The number of people who were infected for first-time was 697, accounting for 55.58%; 29 people were re-infected, accounting for 1.99%; There were 119 patients with unwell symptoms but no nucleic acid test, accounting for 9.49%.Through correlation test and multivariate logistic analysis, it was found that senior grades and underlying diseases were the possible factors that caused the infection and severity of COVID-19. Conclusion The overall vaccination of middle school students in the region is relatively good. Grade and whether there is a basic disease are related to whether they are infected with COVID-19, and whether there is a basic disease is related to reinfections. It is recommended to pay attention to the basic diseases of middle school students and maybe explore the opening of 12-year compulsory education in response to the severe infection situation in third grade.At the same time, we should carry out scientific, effective and dynamic closed-loop health management for middle school students.